2016
DOI: 10.1002/hyp.10913
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of river water temperature: a comparison between a new family of hybrid models and statistical approaches

Abstract: Abstract:River water temperature is a key physical variable controlling several chemical, biological and ecological processes. Its reliable prediction is a main issue in many environmental applications, which however is hampered by data scarcity, when using datademanding deterministic models, and modelling limitations, when using simpler statistical models. In this work we test a suite of models belonging to air2stream family, which are characterized by a hybrid formulation that combines a physical derivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
107
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 56 publications
4
107
0
Order By: Relevance
“…Statistical models require less input data and are usually easier to use, but their lack of physical basis is often seen as a limit to the validity of their predictions in the context of climate change studies (e.g. Piccolroaz et al, 2016). On the contrary, more credit is generally given to the long-term forecasts of the deterministic (2000) hourly, daily forested catchments in Canada UBC Morrison et al (2002) hourly large river basins GISS GCM Ferrari et al (2007) monthly large river basins SWAT Ficklin et al (2012) daily, monthly medium-to large-scale catchments MIKE-SHE MIKE11 Loinaz et al (2013) hourly (Ficklin et al, 2014) -than that of the statistical models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical models require less input data and are usually easier to use, but their lack of physical basis is often seen as a limit to the validity of their predictions in the context of climate change studies (e.g. Piccolroaz et al, 2016). On the contrary, more credit is generally given to the long-term forecasts of the deterministic (2000) hourly, daily forested catchments in Canada UBC Morrison et al (2002) hourly large river basins GISS GCM Ferrari et al (2007) monthly large river basins SWAT Ficklin et al (2012) daily, monthly medium-to large-scale catchments MIKE-SHE MIKE11 Loinaz et al (2013) hourly (Ficklin et al, 2014) -than that of the statistical models.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, more credit is generally given to the long-term forecasts of the deterministic (2000) hourly, daily forested catchments in Canada UBC Morrison et al (2002) hourly large river basins GISS GCM Ferrari et al (2007) monthly large river basins SWAT Ficklin et al (2012) daily, monthly medium-to large-scale catchments MIKE-SHE MIKE11 Loinaz et al (2013) hourly (Ficklin et al, 2014) -than that of the statistical models. It should be mentioned that an intermediate sort of model, referred to as hybrid, has recently been developed (Gallice et al, 2015;Toffolon and Piccolroaz, 2015) and shown by Piccolroaz et al (2016) to be suitable for climate change studies. As opposed to the separate simulation of discharge and stream temperature, the coupled modelling of the two offers new perspectives to investigate the effects of climate change on mountain hydrology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Their main objections to regressive methods arose when modelling reaches of regulated rivers, but this is not our case. In addition, our model improves the models that were tested in both studies (Arismendi et al, 2014;Piccolroaz et al, 2016). Performance indicators of our models produce good results, showing that the models are sufficiently competent.…”
Section: Stream Temperaturementioning
confidence: 65%
“…Arismendi et al (2014) hold that regression models based on air temperature can be inadequate for projecting future stream temperatures because they are only surrogates for air temperature, whereas Piccolroaz et al (2016) argued that the adequacy depends on the hydrological regime, type of model and the timescale analysis. Their main objections to regressive methods arose when modelling reaches of regulated rivers, but this is not our case.…”
Section: Stream Temperaturementioning
confidence: 99%
“…Rabi et al, 2015) have been developed successfully for data relating to different time 99 scales in the past years. Although these statistical models, which link water to air temperatures 100 provide quite simple approaches for water temperature prediction, other statistical models, such 101 as Box Jenkins and non-parametric models (Benyahya et al, 2007), and hybrid statistical-102 physical based models as air2water (Toffolon and Piccolroaz, 2015;Piccolroaz et al, 2016) Piotrowski et al, 2015). DeWeber 107 and Wagner (2014) developed an ANN ensemble model to predict the mean daily water 108 temperature using air temperature, landform attributes and forested land cover as predictors.…”
mentioning
confidence: 99%